1999
DOI: 10.1002/(sici)1097-4687(199903)239:3<245::aid-jmor2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of rhinoceros platelets

Abstract: Basic hematological information about rhinoceros species is limited. In this study, we have determined the platelet counts and described the platelet morphology of free‐living white (Ceratotherium simum) and black (Diceros bicornis) rhinoceros using light and electron microscopy. The platelet counts of the two species were similar, but there were significant differences in platelet size as well as morphology between the species. The presence of large, nondiscoid platelet forms, resembling proplatelet or stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Typically, most platelets of the Arabian oryx, exhibited between 1–2 electron‐dense bodies (Figure ), similar to the number found in the Arabia tahr (Johnson et al, ) but unlike those in humans and camels with 5–7 electron‐dense bodies per cell (Gader et al, ) Electron‐dense bodies have also been reported in other wild and domestic animal species including the white and black rhinoceros (Du Plessis et al, ) and buffalo (Du Plessis et al, ). They are characterized as being clear vesicles with an electron‐dense core.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Typically, most platelets of the Arabian oryx, exhibited between 1–2 electron‐dense bodies (Figure ), similar to the number found in the Arabia tahr (Johnson et al, ) but unlike those in humans and camels with 5–7 electron‐dense bodies per cell (Gader et al, ) Electron‐dense bodies have also been reported in other wild and domestic animal species including the white and black rhinoceros (Du Plessis et al, ) and buffalo (Du Plessis et al, ). They are characterized as being clear vesicles with an electron‐dense core.…”
Section: Resultssupporting
confidence: 65%
“…This cytoskeleton structure gives rigidity and maintains the discoid shape of the platelets (Patel‐Hett et al, ). Approximately, 2 per cent of the platelets exhibited pseudopodia, as described for platelets from humans (van Rooy & Pretorius, ),and infrequently in platelets of impala (Du Plessis, Botha, & Stevens, ) and white and black rhinoceroses (Du Plessis et al, ).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations